Designing AWS environments architect large-scale cloud infrastructures with AWS - Soni, Mitesh; Gilchrist, Wayde (Packt Publishing Ltd., 2018)
Design and create robust and resilient distributed solutions with AWS Key Features Design and secure virtual private network environments on the AWS cloud Deploy appropriate instance types and sizes based on performance and cost requirements Gain proficiency and confidence when designing virtual cloud environments Book Description Amazon Web Services (AWS) provides trusted, cloud-based solutions to help you meet your business needs. Running your solutions in the AWS Cloud can help you get your applications up and running faster while providing the security to meet your compliance requirements. This book begins by familiarizing you with the key capabilities to architect and host applications, websites, and services on AWS. We explain the available options for AWS free tier with virtual instances and demonstrate how you can launch and connect them. Using practical examples, you'll be able to design and deploy networking and hosting solutions for large deployments. Finally, the book focuses on security and important elements of scalability and high availability using AWS VPC, Elastic Load Balancing, and Auto scaling. By the end of this book, you will have handson experience of working with AWS instances, VPC, Elastic Load Balancing, and Auto scalingrelated tasks on Amazon Web Services. What you will learn Establish how to launch EC2 instances and log in Work with Linux and Windows instances Understand Amazon VPC networking creation with and without a wizard Design, create, and secure a Virtual Private Cloud Autoscale instances based on the increase and decrease in traffic Deploy applications in a highly available and fault-tolerant manner Load balance the requests with Elastic Load Balancing Make your applications highly available through load balancing, multi-AZ deployments, and auto scaling Who this book is for This book is for new and aspiring individuals who are preparing or gearing up for a solutions architect role. You'll also find this useful if you're an IT professional such as beginners, cloud architects, and cloud solution providers, or DevOps engineer who is preparing to design and deploy large solutions on AWS. No experience with AWS is required.
Online resource; title from title page (viewed November 5, 2018)
Keywords: Amazon Web Services (Firm); Web services; Cloud computing; Services Web; Infonuagique